Experimental evaluation of impact mode multiple piezoelectric power generator - Basari, Amat Amir; Yan, Ng Xue (2023)
This paper presents the evaluation of energy generation over wide operating frequency bandwidth with two piezoelectric discs working in impact mode. The main structure of the power generator consists of vibrating beam with hitting tip, base beam, and spacers. The output of two of this power generators is combined in parallel and series connection. The output voltage as well as the power generated by this power generator is recorded. The results show that a wider operating frequency bandwidth can be obtained using the developed power generator.